Role of serum response factor expression in prostate cancer biochemical recurrence. Issue 10 (2nd April 2018) - Prencipe, Maria; Fabre, Aurelie; Murphy, Thomas Brendan; Vargyas, Eszter; O'Neill, Amanda; Bjartell, Anders; Tasken, Kristin Austlid; Grytli, Helene H.; Svindland, Aud; Berge, Viktor; Eri, Lars M.; Gallagher, William; et al.
Abstract : Background: Up to a third of prostate cancer patients fail curative treatment strategies such as surgery and radiation therapy in the form of biochemical recurrence (BCR) which can be predictive of poor outcome. Recent clinical trials have shown that men experiencing BCR might benefit from earlier intervention post‐radical prostatectomy (RP). Therefore, there is an urgent need to identify earlier prognostic biomarkers which will guide clinicians in making accurate diagnosis and timely decisions on the next appropriate treatment. The objective of this study was to evaluate Serum Response Factor (SRF) protein expression following RP and to investigate its association with BCR. Materials and Methods: SRF nuclear expression was evaluated by immunohistochemistry (IHC) in TMAs across three international radical prostatectomy cohorts for a total of 615 patients. Log‐rank test and Kaplan‐Meier analyses were used for BCR comparisons. Stepwise backwards elimination proportional hazard regression analysis was used to explore the significance of SRF in predicting BCR in the context of other clinical pathological variables. Area under the curve (AUC) values were generated by simulating repeated random sub‐samples. Results: Analysis of the immunohistochemical staining of benign versus cancer cores showed higher expression of nuclear SRF protein expression in cancer cores compared with benign for all the three TMAs analysed ( P < 0.001, n = 615). Kaplan‐Meier curves of the three TMAs combined showed that patients with higher SRF nuclear expression had a shorter time to BCR compared with patients with lower SRF expression ( P < 0.001, n = 215). Together with pathological T stage T3, SRF was identified as a predictor of BCR using stepwise backwards elimination proportional hazard regression analysis ( P = 0.0521). Moreover ROC curves and AUC values showed that SRF was better than T stage in predicting BCR at year 3 and 5 following radical prostatectomy, the combination of SRF and T stage had a higher AUC value than the two taken separately. Conclusions: SRF assessment by IHC following RP could be useful in guiding clinicians to better identify patients for appropriate follow‐up and timely treatment.